2016
DOI: 10.17984/adyuebd.306387
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Matematiğe Yönelik Öz-yeterlik Algılarının Belirlenmesi: Kaygı ve Tutum Faktörleri

Abstract: This study aims to analyze the anxiety, attitude and self-efficacy perceptions of middle school students towards mathematics and to reveal the relations between these three affective variables. This correlational study is carried out with 246 students studying at a state middle school in Turkey. Mathematics Anxiety Scale, Mathematics Self-Efficacy Perception Scale and Mathematics Attitude Scale were used as data collection tools. Descriptive and inferential statistics were executed to the obtained data. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
0
4
0
4
Order By: Relevance
“…The middle school students' math self-efficacy perceptions were found to be over the median value. In the study conducted by Doruk, Öztürk, and Kaplan (2016), the middle school students' math self-efficacy perceptions were found to be high. In their study, Abalı- Öztürk and Şahin (2015) found that the 5 th grade students' math self-efficacy is high.…”
Section: Discussionmentioning
confidence: 94%
“…The middle school students' math self-efficacy perceptions were found to be over the median value. In the study conducted by Doruk, Öztürk, and Kaplan (2016), the middle school students' math self-efficacy perceptions were found to be high. In their study, Abalı- Öztürk and Şahin (2015) found that the 5 th grade students' math self-efficacy is high.…”
Section: Discussionmentioning
confidence: 94%
“…The study also suggests a theoretical model related to relationships between mathematics anxiety (positive and negative anxiety), perceived mathematics self-efficacy, and learned helplessness in mathematics. Because, some studies show that anxiety is a powerful variable which impacts one's self-efficacy (Pajares, 2003;Doruk, Öztürk & Kaplan, 2016). Further, low self-efficacy may lead to learned helplessness (Ekinci & Gökler, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the findings obtained from the study, the students stated that their anxiety would decrease when they have a good command of the field knowledge and they have confidence in themselves. Doruk, Öztürk and Kaplan (2016), on the other hand, found in their research that as students' self-confidence increased, their anxiety would decrease. Aschraft and Krause (2007) stated that the reason why students with high anxiety level fail in mathematics lesson is not only anxiety, but also insufficient mathematics knowledge will increase anxiety.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 88%